2021
DOI: 10.1590/s1980-220x2019030903686
|View full text |Cite
|
Sign up to set email alerts
|

Association between depressive symptoms and quality of life in outpatients and inpatients with heart failure

Abstract: Objective: To analyze sociodemographic and clinical characteristics, depressive symptoms and quality of life of patients with heart failure and associate quality of life with depressive symptoms. Method: A cross-sectional study conducted with outpatients and inpatients. Sociodemographic data were collected and questionnaires were applied to assess quality of life (Minnesota Living with Heart Failure Questionnaire) and depressive symptoms (Beck Depression Inventory). Results: The sample consisted of 113 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
2
0
2
Order By: Relevance
“…A previous Brazilian study also found that QoL was more affected in the physical dimension when the patients had moderate to severe depressive symptoms (Tinoco et al, 2021), which is consistent with the findings of an Italian study that identified a strong independent association between depression and physical capacity (Chiala et al, 2018).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…A previous Brazilian study also found that QoL was more affected in the physical dimension when the patients had moderate to severe depressive symptoms (Tinoco et al, 2021), which is consistent with the findings of an Italian study that identified a strong independent association between depression and physical capacity (Chiala et al, 2018).…”
supporting
confidence: 87%
“…Recent literature indicates rates of cachexia among Brazilians hospitalized with HF of up to 48.1% and 61.8% have malnutrition (Tinoco et al, 2021). From the patients’ perspective, effective treatment for loss of appetite is an area that requires quality improvement in HF care (Ängerud et al, 2017) and in the care delivered to older adults in general who are hospitalized (Brunner et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A fadiga e a dispneia são os principais sintomas que podem repercutir na realização de atividades da vida diária e social desses indivíduos. Além dos comprometimentos físicos, pacientes com IC podem apresentar sintomas depressivos que diminuem sua capacidade para o autocuidado, levando à baixa adesão ao tratamento da doença e à piora do quadro clínico geral, fatores que aumentam o risco de internações recorrentes 34,35 .…”
Section: Discussionunclassified
“…Ao realizar a análise da associação da síndrome depressiva com a QV dos entrevistados, constatou-se em ambos os instrumentos aplicados que a pior QV esteve significantemente associada à presença de sintomas depressivos. Essa mesma relação foi encontrada em outros estudos, em que os achados evidenciaram que os sintomas de depressão e de ansiedade contribuem para piora da QV relacionada aos sintomas físicos da IC 15,31,32 .…”
Section: Discussionunclassified